Is there a business case for sustainable innovation in the consumer electronics retail industry? - Hannington, Lee Anthony (2007)
Sustainability is about the preservation of economic growth, social justice and environmental resources. Sustainable innovation is innovation, which furthers the continuation of these three pillars. Business traditionally focuses on the financial pillar, making this its top priority. Since this is the case, is there a financial argument (business case) for innovation, which also furthers the development of the other two pillars in the consumer electronics retailing industry?